A Study of Hypothyroidism in Chronic Kidney Disease (CKD) Patients - Sudharsanan V; Prabhu Shankar S; Viknesh V (National Board of Examinations Journal of Medical Sciences)
Introduction: Chronic kidney disease (CKD) is a progressive condition affecting over 800 million people worldwide, primarily attributed to diabetes, hypertension, and other risk factors. The progression of CKD leads to significant complications, including cardiovascular disease, anemia, and metabolic bone disorders. Hypothyroidism, a condition marked by deficient thyroid hormone levels, is known to affect patients with CKD through impacts on thyroid metabolism. Materials and Methods: A hospital-based cross-sectional study was conducted over three months in a tertiary care center in South India. The study involved 237 CKD patients who provided informed consent and met inclusion criteria. Patients with medication histories that could influence thyroid function or those with acute kidney injury were excluded. Detailed clinical assessments and laboratory analyses of renal and thyroid functions were performed. Results: The study population had a mean age of 50.6 years, with 61.2% females. Hypothyroidism was observed in 27.4% of the patients, predominantly subclinical (22.36%) rather than overt hypothyroidism (5.06%). CKD severity correlated significantly with hypothyroidism prevalence, with increased hypothyroidism rates in advanced CKD stages (p < 0.001). Correlation analysis revealed a negative association between estimated glomerular filtration rate (eGFR) and TSH (r = -0.147, p = 0.023), suggesting declining kidney function aligns with thyroid dysfunction. Conclusion: This study highlights a notable correlation between CKD progression and the occurrence of hypothyroidism, particularly subclinical hypothyroidism. Findings suggest a need for routine thyroid evaluation in CKD patients to facilitate early detection and management of thyroid related complications, improving patient outcomes.